Partnerships and pathways to Aboriginal success : Aboriginal service plan: Submitted to the Ministry of Advanced Education September 27, 2007 - Thompson Rivers University (Author) (Thompson Rivers University, 2007)
Thompson Rivers University is located in traditional Shuswap and Cariboo territories and serves the constituent bands as well as neighbouring Nlaka'pamux, St'at'imc, Tsilhgot'in, and Metis nations in addition to many urban Aboriginals. As a consequence, the university has had a long history of involvement with First Nations' tribal councils, bands, and cultural and educational organizations. First as Cariboo College and later as the University College of the Cariboo, the institution has provided education and training services to thousands of both on-and off-campus First Nations and Aboriginal students over the past three decades. However, given its new status as a university, TRU has an opportunity - and an obligation - to forge yet closer links with its urban and rural Aboriginal communities and to develop its existing partnerships, programs, and services to better serve First Nations' communities, Aboriginal organizations and individuals as they work to meet their economic, educational and social goals. Not peer reviewed Planning document